Pancreatitis in pregnancy: The complex interplay with triglycerides and diabetes - Boda, Parisha; Saxena, Harshal; Suthar, Nilay; Bhati, Adityasinh (Asian Journal of Medical Sciences, 2024)
A rare and complex condition, severe gestational hypertriglyceridemia with acute pancreatitis in a primigravida poses a significant therapeutic challenge due to the absence of established guidelines. Many patients with hypertriglyceridemia exhibit concomitant insulin resistance, obesity, and fasting hyperchylomicronemia. This case report explores the successful management of a 20-year-old primigravida at 7 months of pregnancy presenting with severe gestational hypertriglyceridemia, diabetic ketoacidosis, and acute pancreatitis. Despite a lack of prior complications, the patient exhibited metabolic acidosis, hyperglycemia, hypertriglyceridemia, and acute kidney injury. A multifaceted approach involving insulin, statins, fenofibrate, antibiotics, and supportive measures resulted in improved lipid profiles and blood glucose levels. With induced labor and vaginal delivery, the intrauterine fetal death was addressed. The importance of routine lipid profile screening in high-risk pregnancies is underscored, emphasizing the need for early recognition and aggressive multidisciplinary management of severe metabolic complications in pregnant individuals with acute pancreatitis. This case stresses the critical role of a comprehensive approach for a successful outcome in such cases.